Pedagogical System for forming the social health of children and youth - Tsybanyuk, Oleksandra (My University, 2024)
The present academic paper is devoted to developing and implementing educational systems for the formation of social health of children and youth. Social health is defined in this context as a multifaceted concept that includes social skills, emotional intelligence, stress management, civic responsibility and tolerance. The primary purpose of the present research is to develop a pedagogical system that would contribute to forming and maintaining the social health of children and youth. Pedagogical approaches in the education system are distinguished, namely: psychological and pedagogical, socio-cultural, health-preserving, interactive, ecological and gender approaches. It has been determined that the formation of children’s social health is ensured through such aspects as the development of social skills by means of interactive activities and group work, training of emotional intelligence through professional exercises and learning stress management methods. The conducted research provides a valuable scientific and practical elaboration in the field of developing and implementing educational approaches to the formation of social health of children and youth. It has been emphasized that the established educational system for forming the social health of children and youth is comprehensive and systematic
Keywords: Social health, Pedagogical system, Children and youth, Interpersonal communication, Socio-cultural adaptation, Innovative methods, Collaboration between family and education